Persepsi Mahasiswa Farmasi Terhadap Pengobatan Tradisional Majappi-Jappi - Rahayu, Nur Alam; Saputra, Hadi; Hasapri, Fadillah Kurnia Ananda; Nur, Andi Asywid; Istiqfarah, Annisa; Rahayu, Gita; Riswan, Muh (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to understand the perceptions of pharmacy students at Universitas Muhammadiyah Makassar towards the traditional medicine Majappi-Jappi. This research is qualitative, using a phenomenological approach. The determination of informants in this study used purposive sampling, with 15 pharmacy students from the class of 2023 as informants. Data collection was carried out by combining interviews with observations. The results of this study indicate that pharmacy students at Unismuh Makassar have diverse perceptions of Majappi-Jappi traditional medicine, which are divided into three main categories: pro, neutral, and contra. (1) Students who support traditional Majappi-Jappi medicine emphasize that this method has minimal side effects, is supported by family beliefs, and personal experience. (2) Students who are neutral tend to recognize the benefits of both types of treatment, both traditional and modern. They choose the type of treatment based on specific situations or health conditions, while advocating for further scientific research on traditional medicine to understand its benefits and potential risks. (3) Students who prefer modern medicine consider it more efficient, clinically tested, and more accessible.